Evaluation of the Performance of the Investment and Integrated One-Stop Service Department (DPMPTSP) of Sidenreng Rappang Regency Through Public Satisfaction Survey - Ammar, Muhammad Ammar; Nurfajri Ardianti (Universitas Ichsan Sidenreng Rappang, 2025)
This research aims to evaluated the performance of the Investment and One-Stop Integrated Services department (DPMPTSP) of Sidenreng Rappang Regency through a community satisfaction survey. The method used in this research is employing a descriptive analysis approach, inferential analysis such as correlation analysis and quadrant analysis, and adding qualitative analysis using Word Cloud. In addition, the indicators used and the measurement procedures refer to the guidelines of Permenpan RB No. 14 of 2017. The data collection technique began with accidental sampling, selecting samples from individuals who are randomly encountered at the location and have just been served by the DPMPTSP, followed by filling out a questionnaire through face-to-face interviews. Based on the research results, the Public Satisfaction Index (IKM) of DPMPTSP obtained a score of 3.101, which falls into the